實習生自評學習成就、實習經驗、與其自我效能關係之探究 The Relationships among the Self-Evaluated Learning Effects, Interning Experiences, and Perceived Self-Efficacy of Interns - 呂文惠 Wen-Hui Lu; 王金國 Chin-Kuo Wang (National Changhua University of Education, 2014)
在本研究中，研究者以Bandura（1977, 1997, 2001）的自我效能觀理論為基礎，探討實習生自評學習成效、實習成就感、社會性支持、實習學校滿意度、以及對師資培育機構的滿意度等因素對實習生教師生涯自我效能感的預測力。本研究以中部地區某師資培育機構之126 位實習生為對象，以自編「實習生教育生涯自我效能量 表」為研究工具，在其實習最後一個月之返校座談時填寫。結果發現在所有預測變項中，自評學習成效以及社會性支持能顯著地預測教師生涯自我效能，而實習教育階段別與公立與私立學校間無顯著差異。研究者也據此提出相關的研究及實務建議。 In this study, the researchers applied the social learning model proposed by Bandura (1977, 1997, 2001) in exploring how the self-evaluated learning effects, perceived internship achievements, social support, satisfaction with internship schools, and satisfaction with teacher education institutes contribute to the self-efficacy of interns. A total of 126 interns participated in this study and completed questionnaires designed by the researchers. The results indicated that self-evaluated learning effects and social support significantly predict self-efficacy when all of the predictive factors were considered. No significant differences among the students interning at different school levels (kindergarten, elementary, and high school) or between the students interning at public and private schools were observed. Practical and theoretical suggestions are provided based on the results.